Impact Analysis of Ecological Environment Pressure on the Sustainable Development of Northwest Tourism Economy - Li, Yijun; Norimah, Rambeli (International Journal of Global Economics and Management, 2024)
Ecological environment pressure is an important factor restricting the sustainable development of the tourism economy in the northwest region. This paper constructs an index system and measurement model for ecological environment pressure and empirically analyzes five provinces and regions in the northwest based on data from 2013 to 2023. The results show that the overall ecological environment pressure in the northwest region is at a moderately high level, with significant regional differences and temporal variations, mainly due to rapid population growth, sustained high economic growth, and unreasonable industrial structure. Further analysis reveals that intensified ecological environment pressure not only affects the quality of life of local residents but also constrains the sustainable development of regional economy and society, including the tourism industry. Therefore, this article proposes comprehensive countermeasures such as strict population control, optimizing industrial structure, vigorously promoting energy conservation and emission reduction, strengthening ecological protection and restoration, encouraging environmental protection technological innovation, and improving the legal and policy system, to continuously alleviate ecological environment pressure and create favorable conditions for the sustainable development of regional tourism economy.